Supply chain performance of robusta coffee produced in the mountainous areas of Temanggung Indonesia - Susanawati; Fauzi Diaz Keenan (BIO Web of Conferences)
The highlands of Temanggung, situated between Mount Sindoro and Mount Sumbing, are extensively planted with robusta coffee. The region’s climate and rainfall conditions are very suitable for robusta coffee production. The distribution of robusta coffee from these mountainous areas in Temanggung is inherently linked to the concept of the supply chain..This research aims to identify the supply chain and performance in by examining product flow, money flow, and information flow. The respondents at the farmer level were located in Gesing, while those at higher levels of the supply chain resided in Temanggung. A total of 171 participants were involved in this study, including 105 farmers, five collectors, two wholesalers, four roasteries, five cafes, and 50 consumers. Descriptive analysis and supply chain performance evaluations were conducted, using a 1 to 5 scale for product and money flows, and a 1 to 2 scale for information flow. The analysis disclosed five chains composed of six distinct actors: farmers, collectors, wholesalers, roasteries, cafes, and consumers. The research results show that the overall performance of robusta coffee supply chain is running well, seen from the smooth of products flow, money flow and information flow.